A β-glucan from Durvillaea Antarctica has immunomodulatory effects on RAW264.7 macrophages via toll-like receptor 4. (1st July 2018) - Yang, Yi; Zhao, Xiaoliang; Li, Jia; Jiang, Hao; Shan, Xindi; Wang, Ya; Ma, Wenbang; Hao, Jiejie; Yu, Guangli
Highlights: The structure of a novel polysaccharide extracted from Durvillaea Antarctica (BG136) is identified as β1, 3/1, 6-glucan. BG136 promotes cytokine production, pinocytosis and TLR4 expression by macrophages. BG136 activates MAPKs and NF-κB signaling pathways through TLR4 receptor. Abstract: We studied the mechanisms underlying the immunostimulatory effects of aβ-1, 3/1, 6-glucan (BG136) from Durvillaea Antarctica . Our data showed that BG136 promoted the activation of MAPKs and NF-κB signaling pathways and cytokines production. BG136 did not increase MCP-1 or NO production or phosphorylation of NF-κB and MAPK in TLR4 siRNA knockdown cells, indicating that BG136 activates macrophages through TLR4. Flow cytometry analysis and confocal experiment showed that BG136 bound to TLR4 expressed on RAW264.7 macrophage cells surface. The affinity of BG136 for TLR4 was determined using Surface Plasmon Resonance (SPR) (KD: 4.51 × 10 −6M ). Altogether, our results showed that BG136 activates RAW264.7 cells by binding to TLR4 and then triggering TLR4-mediated signaling pathways to promote cytokines secretion.